Characterization of Nanolayer Intermetallics Formed in Cold Sprayed Al Powder on Mg Substrate - Shaha, Sugrib Kumar (Materials (Basel), 2019)
Supersonic impact of particles in their solid state with substrate at a low temperature creates a complex bonding mechanism and surface modification in cold spray coating. Here, we report the formation of a layer of 200 to 300 nm intermetallic at the interface of cold spray coated AZ31B-type Mg alloy with AA7075-type Al alloy powder. XRD, SAED, and FFT analysis confirmed the layer possessed BBC crystal structure of Mg(17)Al(12) intermetallic. The HR-TEM image analysis at the interface identified the BBC crystal structure with interplanar spacing of 0.745 nm for (110) planes, suggesting the Mg(17)Al(12) phase. The nanoindentation tests showed that the hardness at the interface was ~3 times higher than the substrate. It was also noticed that Young’s modulus at the interface was 117GPa. The combined action of impact energy and carrier gas temperature, along with the multiple passes during coating, caused the formation of intermetallic.